The Rising Religious Extremism and Mob violence in Nigeria - Ismail Husain Mshelia (Clinical Sociology Review)
Before the emergence of Boko haram terrorist group in the early 2000s, religious extremism in Nigeria had sparked large scale crises in Kaduna and Plateau among other states in the country. Since the inception of the Nigerian fourth republic, such crises have been undermining public safety and by implication, the country’s quest for national integration and sustainable development. In the light of a mob violence that resulted in the gruesome murder of a college student who allegedly uttered blasphemous comment, this paper examined the rise of religious extremism in Nigeria. Looking beyond human security threats like poverty and illiteracy, the paper utilised desk review of published documents to establish the historical and political factors that sowed in the country, the seeds of religious extremism now germinating. The paper found that the nature of the pre-colonial empires that now make up the Nigerian state coupled with colonial and post-colonial factors including the dissipation of knowledge on Islamic justice system, competition over political powers and the politics of divide and rule have converged to make religion a volatile phenomenon in the country. Therefore, the paper concludes that until the multidimensional factors are addressed through mitigating and preventive efforts—such as robust religious education, religious regulation, interreligious dialogue and economic empowerment—the country’s quest for ‘peace, justice and strong institutions’ among other Sustainable Development Goals (SDGs) will remain a mirage.